Integrating climate and land‐use change scenarios in modelling the future spread of invasive squirrels in Italy. Issue 4 (10th January 2019) - Di Febbraro, Mirko; Menchetti, Mattia; Russo, Danilo; Ancillotto, Leonardo; Aloise, Gaetano; Roscioni, Federica; Preatoni, Damiano G.; Loy, Anna; Martinoli, Adriano; Bertolino, Sandro; Mori, Emiliano
Abstract: Aim: The establishment and spread of invasive alien species may be influenced by several mutually interacting factors, whose understanding is paramount to develop effective biosecurity policies. However, studies focused on modelling spatially explicit patterns of future invasion risk have so far focused on species response to climate change impacts, while land‐use change has been neglected. We investigated how the interplay between climate and land‐use change could affect the future potential distribution and dispersal corridors of four alien squirrels introduced to Europe ( Sciurus carolinensis, Callosciurus finlaysonii, Callosciurus erythraeus and Eutamias sibiricus ). Location and Methods: Our study was conducted in Italy. We used Species Distribution Models and circuit theory methods to test whether future scenarios based only on climate change predict a different effect on range and connectivity of alien squirrel populations, compared to scenarios that include both climate and land‐use changes. Results: Scenarios based only on climate change predicted a range increase and a high geographic stability (>50%) for most species, with different, yet limited, effects on connectivity corridors. Conversely, scenarios based on both climate and land‐use change showed a loss in range extent and a low geographic stability (<50%) of both range and dispersal corridors for most species. Main conclusions: Scenarios considering both climate and land‐use change provide predictions on invasion risk that overturn those including only climate change. The effect of global warming alone would lead to a considerable range expansion of all species. Conversely, when land‐use change is added, a potential loss in suitable habitat and dispersal corridors is predicted for alien squirrels, hence limiting their range expansion. We recommend using multiple drivers in models to obtain reliable predictions for implementing biosecurity policies related to invasive alien species.